Posterior Reversible Encephalopathy Syndrome; An Unusual Manifestation of Systemic Lupus Erythematosus: A Case Report - Talukder, Manik Kumar; Islam, Md Imnul; Begum, Suraiya; Kundu, Gopen Kumar; Rahman, Shahana (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v35i3.10525 Bangladesh J Child Health 2011; Vol 35 (3): 124-126